A study of the prevalence of Hepatitis B virus infection in the infants of HIV-positive mothers participating in P1041 in South Africa - Tamandjou Tchuem, Cynthia Raissa (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScMedSc)--Stellenbosch University, 2014.